Musculoskeletal Pain in Parkinson's Disease - Li, Jun; Zhu, Ben-Fan; Gu, Zhu-Qin; Zhang, Hui; Mei, Shan-Shan; Ji, Shao-Zhen; Liu, Shu-Ying; Han, Chao; Chen, Huai-Zhen; Chan, Piu (Frontiers in Neurology, 2022)
Background Musculoskeletal pain is commonly experienced in patients with Parkinson's disease (PD). Few studies have investigated the clinical characteristics and risk factors associated with musculoskeletal pain. Objectives To investigate the distribution, clinical characteristics, and factors associated with musculoskeletal pain in a large sample of patients with PD. Methods We enrolled 452 patients from two clinics and used a standardized questionnaire to collect demographic and clinical information. Musculoskeletal pain was diagnosed based on the Ford Classification System, and pain severity was assessed with the numeric rating scale (NRS). Multivariate regression models explored the association between clinical features of PD and quality of life and pain. Results Two hundred and six patients (45.58%) reported musculoskeletal pain, typically in their lower limbs and backs. Levodopa resulted in a ≥30% reduction in pain intensity scores in 170 subjects. Female sex (odds ratio [OR], 1.57; 95% CI, 1.07–2.29) and Levodopa-equivalent daily doses (LEDDs; OR, 3.35; 95% CI, 1.63–6.59) were associated with an increased risk for musculoskeletal pain. Pain duration (p = 0.017), motor symptoms (p < 0.001), and depression (p < 0.001) were significantly associated with quality of life. Conclusions The lower limbs and back are common sites of musculoskeletal pain in patients with PD, and up to 82.52% of patients were responsive to Levodopa. Female sex and LEDDs are associated with musculoskeletal pain, suggesting that dopamine deficiencies, and not the motor and non-motor impairment, might be the most critical baseline risk factor of musculoskeletal pain.